Tachinus flavimaculatus, a new species of the subgenus Tachinoderus Motschulsky from China (Coleoptera: Staphylinidae: Tachyporinae) - Feng, Yong-Yan; Yin, Zi-Wei (Zootaxa, 2021)
Tachinus flavimaculatus Feng & Yin, sp. nov., a new species of the T. nepalensis Ullrich group of the subgenus Tachinoderus Motschulsky, is described from southeastern Xizang, China, with habitus and major diagnostic features illustrated.